Influence of muscarinic M1 receptor antagonism on brain choline levels and functional connectivity in medication-free subjects with psychosis: A placebo controlled, cross-over study. (30th August 2019) - Vingerhoets, Claudia; Bakker, Geor; Schrantee, Anouk; van der Pluijm, Marieke; Bloemen, Oswald J.N.; Reneman, Liesbeth; Caan, Matthan; Booij, Jan; van Amelsvoort, Therese A.M.J.
Highlights: The first in-vivo study examining muscarinic M1 receptor modulation in psychosis. Choline concentrations did differ between psychotic patients and healthy controls. Functional connectivity did not differ between psychotic patients and controls. M1 modulation did not influence choline levels in both groups. M1 modulation did not influence functional connectivity in both groups. Abstract: An increasing number of studies implicate the muscarinic cholinergic system in cognitive dysfunction associated with psychosis. This study examined the effect of muscarinic M1 receptor modulation on anterior cingulate cortex (ACC) and striatal choline concentrations and the relation with cognitive performance, as well as functional connectivity of cognitive networks. Thirty medication-free subjects with a psychosis spectrum disorder and 30 gender, age and IQ-matched healthy control subjects underwent 1 H-proton magnetic resonance spectroscopy ( 1 H-MRS) twice, once after placebo and once after a single dose of biperiden (M1 receptor antagonist, 4 mg). A subset of 19 psychotic subjects and 28 controls underwent resting-state functional magnetic resonance imaging (rs-fMRI) as well. No significant differences were found in ACC and striatal choline levels, nor in functional connectivity, between the two groups after placebo. Moreover, M1 antagonism did not significantly affect choline levels or functional connectivity. No correlations were found between choline levels and cognition as well as psychotic symptoms. Our findings do not support an association between the cholinergic system and cognition and psychotic symptoms. However, the lack of group differences in choline concentrations and functional connectivity, both after biperiden and placebo, may indicate that there were no severe cholinergic abnormalities present in our sample.